Acrodermatitis Continua of Hallopeau and Generalised Pustular Psoriasis: Case Reports of Two Different Manifestations of IL36RN Mutation in Siblings - Gu M; Huang H; Xiao Z; Meng F; Sheng H; Lin Z; Li C; Wu Y (Psoriasis: Targets and Therapy)
Mengjiao Gu,1,2,* Hanjing Huang,1,2,* Zhanshuo Xiao,3,* Fanzhang Meng,4 Han Sheng,4 Zhimin Lin,5 Chen Li,6,7 Yuanhao Wu1,2 1First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China; 2National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, Tianjin, People’s Republic of China; 3Department of Dermatology, Guang’anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, People’s Republic of China; 4School of Clinical Medicine, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 5Third Affiliated Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 6Department of Rheumatology, Fangshan Hospital Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 7Department of Dermatology, Tianjin Institute of Integrative Dermatology, Tianjin Academy of Traditional Chinese Medicine Affiliated Hospital, Tianjin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chen Li, Fangshan Hospital Beijing University of Chinese Medicine, Beijing, China; Tianjin Academy of Traditional Chinese Medicine Affiliated Hospital, Tianjin, People’s Republic of China, Tel +86 010 13810988688, Email casio1981@163.com Yuanhao Wu, First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China, Tel +86 022 16622507882, Email doctor.wuyh@gmail.comAbstract: In our manuscript, we present a case study of siblings with Generalized Pustular Psoriasis (GPP) and Acrodermatitis Continua of Hallopeau (ACH), both harboring IL36RN gene mutations. The 3-year-old proband exhibited systemic pustules leading to a GPP diagnosis, while his 6-year-old sister developed nail ulcers and subungual pustules characteristic of ACH. Despite standard treatments, their conditions were refractory. Genetic analysis revealed a homozygous splice variant c.115+6 T>C, with heterozygous parents. This case underscores the role of IL36RN mutations in pustular psoriasis and supports ACH as a localized form of the disease. The distinct subtypes in siblings with identical mutations suggest a complex pathogenesis influenced by additional factors. Our findings highlight the importance of genetic testing in pustular psoriasis and warrant further investigation into the phenotypic variability of IL36RN-related disease.Keywords: Acrodermatitis Continua of Hallopeau, generalised pustular psoriasis, IL36RN gene mutations